TELAAH KUALITAS AIR DENGAN TEKNOLOGI BERBEDA DAN ANALISIS BAKTERI PATOGEN (Aeromonas salmonicida )PADA IKAN PATIN DI KECAMATAN BANGKINANG BARAT KABUPATEN KAMPAR PROVINSI RIAU - Fabri Putra Nugraha; Yusni Ikhwan Siregar; Iesje Lukistyowati (Jurnal Ilmu Lingkungan, 2014)
This study was conducted from October to December 2012 at the subdistrict of WestBangkinang, Riau Province. The study aimed to described the basic information ofwater quality in different technology of maintenance (traditional, semi intensive andintensive) catfish in freshwater pond especially the contains of macrozoobenthic. Watersample were taken from three station whereas catfish sample were taken in threelocation and each station consist of 4 heads in each station. The catfish sample will betaken every week for 1 month. The results of (H’) and (C), station 3 had low (H’) withdominanted of (C), and it means they got hard pressure of environment activity.Besides, Aeromonas caviae was found in all technology of maintenance freshwaterponds. The result of Aeromonas salmonicida bacteria, was founded in three sample incatfish of different freshwater pond as A. sub smithia and A. sub achromogenes. Inaddition to measurement of water quality consist of temperature 27,9-28,6 0 C; pH : 5,7-6,4; DO :4,9-5,7 ppm; BOD :11,3-14,7ppm; COD : 14,7-18,2 ppm. Physics andchemistry sediment is muddy more than 65% from each station. According toPP.82/2001 about water quality of aquaculture, it was putted on the 3 rd class.Keywords: Macrozoobenthic, water quality, aeromonas salmonicida